Endoscopic prophylaxis and factors associated with bleeding in children with extrahepatic portal vein obstruction - Ana Paula Pereira de Oliveira; Alexandre Rodrigues Ferreira; Eleonora Druve Tavares Fagundes; Thaís Costa Nascentes Queiroz; Simone Diniz Carvalho; José Andrade Franco Neto; Paulo Fernando Souto Bittencourt (Brazilian Society of Pediatrics, 2020)
Objectives: This study aimed to evaluate factors associated with upper digestive hemorrhage and primary and secondary endoscopic prophylaxis outcomes in children with extrahepatic portal vein obstruction. Methods: This observational and prospective study included 72 children with extrahepatic portal vein obstruction who were followed from 2005 to 2017. Risk factors associated with upper digestive hemorrhage and the results of primary and secondary prophylaxis of these patients were evaluated. Results: Fifty patients (69.4%) had one or more episodes of bleeding during follow‐up, with a median age at first hemorrhage of 4.81 years. The multivariate analysis showed that medium‐ to large‐caliber esophageal varices were associated with an 18‐fold risk of upper digestive hemorrhage (95% CI: 4.33-74.76; p < 0.0001). Primary prophylaxis was administered to 14 patients, with eradication in 85.7%; however, 14.3% of these patients had hemorrhages during the follow‐up period and 41.7% had a relapse of varices. Secondary prophylaxis was administered to 41 patients. Esophageal varices were eradicated in 90.2% of patients. There were relapse and re‐bleeding of esophageal varices in 45.9% and 34.1% of the children, respectively. Conclusion: Primary and secondary endoscopic prophylaxes showed high rates of esophageal varix eradication, but with significant relapses. Eradication of esophageal varices cannot definitively prevent recurrent upper digestive hemorrhage, since bleeding from alternate sites can occur. Medium‐ and large‐caliber esophageal varices were associated with upper digestive hemorrhage in patients with extrahepatic portal vein obstruction. To the best of the authors' knowledge, this study is the first to evaluate bleeding risk factors in children with extrahepatic portal vein obstruction. Resumo: Objetivos: Este estudo visou avaliar fatores associados à hemorragia digestiva alta e resultados da profilaxia endoscópica primária e secundária em crianças com obstrução extra‐hepática da veia porta. Métodos: Este estudo observacional e prospectivo incluiu 72 crianças com obstrução extra‐hepática da veia porta acompanhadas de 2005 a 2017. Os fatores de risco associados à hemorragia digestiva alta e os resultados da profilaxia primária e secundária desses pacientes foram avaliados. Resultados: Dos pacientes, 50 (69,4%) apresentaram ≥ 1 episódio de sangramento durante o acompanhamento, com idade média da primeira hemorragia de 4,81 anos. A análise multivariada mostrou que varizes esofágicas de médio a grande calibre estavam associadas a um risco 18 vezes maior de hemorragia digestiva alta (IC de 95% 4,33-74,76; p < 0,0001). Foi administrada profilaxia primária em 14 pacientes, com erradicação em 85,7%; contudo, 14,3% desses pacientes apresentaram hemorragias durante o período de acompanhamento e 41,7% apresentaram recidiva de varizes. Foi administrada profilaxia secundária em 41 pacientes. As varizes esofágicas foram erradicadas em 90,2% dos pacientes. Houve recidiva e novos sangramentos de varizes esofágicas em 45,9% e 34,1% das crianças, respectivamente. Conclusão: As profilaxias esofágicas primárias e secundárias apresentaram altas taxas de erradicação de varizes esofágicas, porém com recidivas significativas. A erradicação de varizes esofágicas não pode prevenir de forma definitiva a hemorragia digestiva alta recorrente, pois pode ocorrer sangramento de outros locais. Varizes esofágicas de médio e grande calibre estavam associadas à hemorragia digestiva alta em pacientes com obstrução extra‐hepática da veia porta. No melhor de nosso conhecimento, nosso estudo é o primeiro a avaliar os fatores de risco de sangramento em crianças com obstrução extra‐hepática da veia porta.